2016
DOI: 10.2147/cia.s99698
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural temporary pacing in primary percutaneous coronary intervention for patients with acute inferior myocardial infarction

Abstract: ObjectiveHigh-degree atrioventricular block (AVB), including complete AVB in acute inferior ST-elevation myocardial infarction (STEMI), is not uncommon. However, there is no study evaluating the clinical differences between patients who have undergone temporary pacing (TP) and patients who have not. The present study was designed to investigate whether TP has any prognostic significance in inferior STEMI complicated by complete AVB.MethodsFrom January 2009 to December 2014, 295 consecutive patients diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As Hwang and others report, in acute inferior STEMI and high-degree atrioventricular block, periprocedural TTCP for primary percutaneous coronary intervention does not decrease the incidence of adverse cardiocerebrovascular events and thus is more likely to increase the incidence of cardiogenic shock and prolong hospitalization. 22 An analysis of >360,000 patients who underwent TTCP in the United States between 2004 and 2014 concluded that TTCP is generally safe with low pericardial complication rates (0.6%). 13 However, the in-hospital mortality rate (>10%) and strikingly high mortality rate (>50%) over 4 years of follow-up are concerning and suggest the need to identify other complications and alterations of TTCP.…”
Section: Discussionmentioning
confidence: 99%
“…As Hwang and others report, in acute inferior STEMI and high-degree atrioventricular block, periprocedural TTCP for primary percutaneous coronary intervention does not decrease the incidence of adverse cardiocerebrovascular events and thus is more likely to increase the incidence of cardiogenic shock and prolong hospitalization. 22 An analysis of >360,000 patients who underwent TTCP in the United States between 2004 and 2014 concluded that TTCP is generally safe with low pericardial complication rates (0.6%). 13 However, the in-hospital mortality rate (>10%) and strikingly high mortality rate (>50%) over 4 years of follow-up are concerning and suggest the need to identify other complications and alterations of TTCP.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the opening of the RCA, AV conduction in these patients usually normalizes. In patients with LAD occlusion, ischemia is usually infra-Hisian, the escape rhythm is usually unstable, which is why implanting a temporary PM is necessary in these patients (2,3,4,6,14,15,16,17,18). In the present study, all the patients who had anterior STEMI and complete AV block had a temporary pacemaker implanted.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were discharged on antiplatelet therapy alone. Risk of subsequent atrial fibril-high-grade AV block complicating AMI is reperfusion therapy [82]. For patients with symptomatic or hemodynamically significant AV block in the setting of MI that is likely due to block at the AV node, atropine is a reasonable intervention [54].…”
Section: Atrial Fibrillation/atrial Fluttermentioning
confidence: 99%
“…Dopamine and epinephrine may be considered in the unstable patient. Aminophylline has shown promise in a small case series, but rigorous data are lacking [47][48][49][50][51][52][53][54][75][76][77][78][79][80][81][82][83]. Temporary pacing is indicated for patients presenting with AMI with significant bradycardia or AV block that is medically refractory or associated with ongoing symptoms [54].…”
Section: Atrial Fibrillation/atrial Fluttermentioning
confidence: 99%